A novel approach for Chaotic image Encryption based on block level permutation and bit-wise substitution - Vidhya, R.; Brindha, M. (Multimedia tools and applications, 2022)
Digital multimedia information is frequently transferred over the Internet due to its widespread usage. A novel Butterfly Network Topology (BNT) based block-level permutation ( B 2 LP) and Crown Graph-based Bit-wise Substitution (CGBS) is proposed in this work to securely transfer images over untrusted networks, such as social networks. First, a plain image related initial vector generation is suggested to obtain good plain image sensitivity to withstand chosen/known plain text attacks. Using these initial vectors, Henon map is iterated to produce the random key sequence values to be utilized over the confusion and diffusion processes. Second, BNT based block-level scrambling is proposed by which the plain image is transformed into blocks to attain the block level confused image. Additionally, simple sorting based confusion is applied to obtain the final confused image. Third, crown graph-based bit-wise diffusion is proposed to attain the final encrypted image. General security measures are carried out for the proposed method to validate its security level. It is shown from the simulations that the suggested approach has good randomness, high key sensitivity, good key space, and flat cipher image pixel distribution. Differential cryptanalysis for the proposed system is also conducted to show its efficacy against differential attacks.